The hypothesis of matching about styles of learning and teaching at Higher Education - Ventura, Ana Clara (2013)
A review of learning and teaching styles matching at university over the last ten years is presented. For this purpose, a review was carried out of the Dialnet, Redalyc, Scielo and Doaj data bases due to their scope and importance in the Hispanic context. The descriptors used in the search for information were the key words: learning styles, teaching styles and higher education. The data bases consulted produced a total of 53 papers, with only 17 of these complying with all the criteria for inclusion (paper: empirical research; sample: university;object: correspondence learning and teaching styles; time period 2002-2012; Spanish language). The literature review showed that the matching is researched and understanding from two approaches: (1) adaptive instruction or (2) stylistics. Results are discussed.